Examining Indonesia’s Aggression towards Malaysia over Tari Pendet Dispute in Youtube Comments: The Role of Collective Narcissism - Hendra, Sarah Pricillia (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2024)
This study analyses themes that emerged in discussions on YouTube comments by Indonesian regarding the 2009 Pendet Dance controversy. The research uses netnography methods with a qualitative approach. Using Netlytic, corpus was collected from YouTube under 'Malaysian Pendet Dance' keyword. There are 1030 comments gathered from 4 relevant videos. The corpus was selected and eliminated to 52 comments. For comparison, the corpus is divided based on the upload period, marked by the time Discovery Channel apologized to Indonesia. Based on collective narcissism understanding, researcher frames the emerging themes and sub-themes related to the nature of collective narcissism. The themes and sub-themes of the comments were then coded, compared, and projected with the help of NVivo software. The results show that there is a development of stacking narcissism themes across periods. The collective narcissism themes found in the 2009 period were aggressiveness; desire for justification and other nations’ recognition of own culture; prejudice which causes hostility. Meanwhile, during the commentary period from 2010 to present, the same themes are found, with the addition of sub-themes and three new main themes namely the hardship of forgetting old wounds; see oneself as a tortured victim; and radicalism-to which brought another issue. The conflict between the Indonesian and Malaysian began in 1963 in the Borneo conflict and still ongoing. The collective narcissism that Indonesian society displays towards Malaysia is mediated by the ideology of blind patriotism and the perceived threat to the group by external aggression.